Catch rate and at‐vessel mortality of circle hooks versus J‐hooks in pelagic longline fisheries: A global meta‐analysis. Issue 3 (15th December 2017) - Reinhardt, James F.; Weaver, Jennifer; Latham, Pamela J.; Dell'Apa, Andrea; Serafy, Joseph E.; Browder, Joan A.; Christman, Mary; Foster, Daniel G.; Blankinship, David R.
Abstract: We conducted a meta‐analysis of literature reporting on the use of circle hooks and J‐hooks in pelagic longline fisheries. Our study included more data than previous meta‐analyses of the effects of hook type, due to both a larger number of relevant studies available in recent years and a more general modelling approach. Data from 42 empirical studies were analysed using a random effects model to compare the effects of circle hooks and J‐hooks on catch rate (43 species) and at‐vessel mortality (31 species) of target and bycatch species. Catch rates with circle hooks were greater for 11 species, including four tuna species, six shark species and one Istiophorid billfish. Catch rates on circle hooks were lower for seven species, including two Istiophorid billfishes and two species of sea turtle. At‐vessel mortality was significantly lower with circle hooks in 12 species, including three tuna species, three Istiophorid billfishes, swordfish ( Xiphias gladius ) and three shark species. No species had significantly greater at‐vessel mortality when captured with a circle hook rather than a J‐hook. While our general approach increased model variability compared to more detailed studies, results were consistent with trends identified in previous studies that compared the catch rates and at‐vessel mortality (between hook types) for a number of species. Our results suggest that circle hooks can be a promising tool to reduce mortality of some bycatch species in pelagic longline fisheries, although the effects depend on the species and the metric (catch rate or at‐vessel mortality), emphasizing the need for fishery‐specific data in conservation and management decisions.